Earliness of spring bread wheat accessions under the conditions of the Middle Volga Region - D-r F. Askhadullin; D-l F. Askhadullin; N. Z. Vasilova; A. N. Brykova (Труды по прикладной ботанике, генетике и селекции)
Background. Development of early-ripening high-yielding cultivars of spring bread wheat is a complicated and difficult process. Striving for higher yields has triggered a trend to prolong the growing season pf the cultivars released by the Tatar Research Institute of Agriculture (TatRIA). Our breeding efforts to produce early cultivars, based on using an early-ripening sample as one of the parents, were unsuccessful. This paper presents a search for solutions to the said problem.Materials and methods. We studied spring bread wheat accessions from the collections of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) and Baicheng Academy of Agricultural Sciences (China) as well as promising lines developed by TatRIA. The study of the material was based on conventional spring bread wheat breeding methods. Phenological phases of wheat development were identified using the Zadoks scale.Results. An ambiguous role played by the vernalization response (Vrn) and photoperiod sensitivity (Ppd) genes in wheat earliness was shown, which is consistent with the data repeatedly presented in other publications. We identified accessions with the shortest period from sprouting to heading. Under our climate conditions, the earliest cultivars were those from Novosibirsk Province, Russia, and the North-Eastern China, where wheat development from sprouting to heading lasted 36–46 days.